Temporary propping at Crossrail Paddington station. Issue 1 (4th March 2016) - Chambers, Paul; Augarde, Charles; Reed, Sam; Dobbins, Adrian
Abstract : The construction of Crossrail Paddington station in London (between 2011 and 2018) required a large temporary propping system, which contained one of the most comprehensive monitoring schemes to date. This paper explores the design and operation of this system through the analysis of a data set collected during the construction period and the numerical modelling undertaken at Durham University. The effects of temperature variation on the partially exposed propping system are quantified, as well as the impact of events in the construction sequence including slab casting, adjacent prop removal and excavation. Several lessons were learned during the construction, in terms of prop installation and removal and the management of the monitoring system. These are discussed for the benefit of future projects using temporary propping and monitoring schemes. The findings from this research have led to a greater understanding of the behaviour of propping systems under different environmental conditions, and may therefore lead to more efficient and safer designs in the future.